(untitled) (European Journal of Interdisciplinary Research and Development, 2024)
There are currently 3 main hypotheses of Global climate change. These are astronomical, physical and geologo-geographical reasons. Astronomical reasons include changes in the eccentricity of the Earth’s orbit, the slope and precession of the Earth’s axis, and we will consider them separately below. Physical causes include causes such as changes in air composition being contaminated by volcanoes. They are clearly manifested in the changes of the climate of the present time.